2020
DOI: 10.3389/fped.2020.597699
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 in Milk From COVID-19 Positive Mothers and Follow-Up of Their Infants

Abstract: Background: In the current SARS-Coronavirus-2 (SARS-CoV-2) pandemic little is known about SARS-CoV-2 in human milk. It is important to discover if breast milk is a vehicle of infection. Objective: Our aim was to look for the presence of SARS-CoV-2 RNA in the milk of a group of SARS-CoV-2 positive mothers from NorthWest Italy. Methods: This is a prospective collaborative observational study where samples of human milk from 14 breastfeeding mothers positive for SARS-CoV-2 were collected. A search of viral RNA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 18 publications
2
53
0
5
Order By: Relevance
“…Breastfeeding transmission would require exposure to infectious breastmilk as well as acquisition via an oral or gastrointestinal route. SARS-CoV-2 RNA has been detected in breastmilk in rare cases [7/141 samples (5%) in 64 women] [15] , [16] , [17] , [18] . One case series reported a negative viral culture of a single RNA-positive milk sample, suggesting that SARS-CoV-2 does not represent replication-competent virus capable of infecting the baby [16] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Breastfeeding transmission would require exposure to infectious breastmilk as well as acquisition via an oral or gastrointestinal route. SARS-CoV-2 RNA has been detected in breastmilk in rare cases [7/141 samples (5%) in 64 women] [15] , [16] , [17] , [18] . One case series reported a negative viral culture of a single RNA-positive milk sample, suggesting that SARS-CoV-2 does not represent replication-competent virus capable of infecting the baby [16] .…”
Section: Discussionmentioning
confidence: 99%
“…One case series reported a negative viral culture of a single RNA-positive milk sample, suggesting that SARS-CoV-2 does not represent replication-competent virus capable of infecting the baby [16] . Studies have reported two infected neonates who received SARS-CoV-2-positive breastmilk [ 17 , 18 ]. Both tested positive after the onset of maternal symptoms whilst rooming-in together; thus, horizontal transmission could not be excluded [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations